Pupil Reactions to Tactile Stimulation: A Systematic Review - Gusso, Mariana de Mello; Serur, Gabriele; Nohama, Percy (Frontiers in Neuroscience, 2021)
Pupil dynamics can represent an indirect measure of perception; thus, it has been broadly explored in the auditory and visual fields. Although it is crucial for experiencing the outside world, tactile perception is not well explored. Considering that, we sought to answer the following question via a systematic review: does normal tactile perception processing modulate pupil dilation in mammals (human or not)? The review process was conducted according to PRISMA-Statement. We searched on Periódicos CAPES (Brazil) for the term: ((touch OR (cutaneous stimulation) OR (tactile perception) OR (somatosensory) AND (pupil OR pupillary) NOT blind NOT reflex NOT pain NOT fear NOT noxious NOT autism NOT nerve NOT (pupillary block) NOT glaucoma NOT cataract NOT aneurysm NOT syndrome NOT treatment NOT special education). From the 6488 papers found, 4568 were duplicates, and nine fulfilled the inclusion criteria. All papers found a positive relationship between pupil diameter and tactile perception. We found that the pupil is a reliable indirect measure of brain states and can evaluate norepinephrine (NE)/ Locus Coeruleus (LC) action, stimulus inhibition, arousal, cognitive processes, and affection independently of the stimuli category (visual, auditory, or tactile). We also found that the perceptual tactile processing occurs in similar ways as the other perceptual modalities. We verified that more studies should be done, mostly avoiding low sampling rate recording systems and confounders as cue signs, not automated stimulation, and concurrent stimulus, and using more reliable equipment.